Synthesis and Characterization of Mixed Ligand Complexes of VO(IV) and ZrO(IV) with 3-Phenyl-5-methoxy indole-2-carboxymidyl Furoinimine as Primary and 3´-(2-Carboxy-phenylazo)-2´-amino Pyridine as Co-Ligand - K. Agarwal, Suresh; Jain, Jaya; Chand Lali, Subhash (Asian Journal of Chemistry, 2016)
Mixed ligand complexes of VO(IV) and ZrO(IV) with 3-phenyl-5-methoxy indole-2-carboxymidyl furoinimine (PMICF) as primary and 3´-(2-carboxy-phenylazo)-2´-amino pyridine (CPAP) as co-ligand have been synthesized and characterized on the basis of analytical, conductance, spectral and thermal data. Analytical data suggested 1 : 1 : 1 (MO-L-L´) stoichiometic composition for all the complexes [where M = V(IV)/Zr(IV), L = PMICF and L´ = CPAP]. Electrolytic conductance data (DM = 72.3–78.6 ohm–1cm2mol–1) of all the complexes of VO(IV) revealed their 1 : 1 electrolytic nature except VO(IV) complex prepared by taking vanadyl sulphate and the above ligands which is non-electrolyte. On the other hand, ZrO(IV) complexes are non-electrolytes. Electronic spectra of VO(IV) complexes showed that they exhibit distorted octahedral configuration. IR spectra showed that the primary ligand (PMICF) acts as a tridentate ligand and the azo compound (CPAP) serves as bidentate ligand. Thermal stabilities of these complexes have also been investigated.